2016
DOI: 10.1007/s00405-016-4398-2
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of intraoperative frozen section during thyroid surgery

Abstract: Retrospective analysis on 312 patients, operated for thyroid nodules between 2014 and 2015, was conducted to evaluate the impact of frozen section analysis on the strategy of thyroid nodule surgery. One hundred and ninety-three patients were included. They all underwent preoperative US, fine needle aspiration cytology (FNAC), per operative frozen section (FS) and post operative definitive pathological analysis. Se, Sp, VPP and VPN of FNAC and FS were calculated and compared (McNemar's test). Multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…is not progressing, so the patient's thyroid cancer will not cause a problem. As a result, microinvasive papillary cancer is not considered even to be malignant [7][8][9][10][11]. According to the results of our study, microinvasive papillary cancer was detected in 26 patients, but of them were found incidentally in goiters with no cancer suspicion preoperatively.…”
Section: Journal Of Endocrinology and Thyroid Researchmentioning
confidence: 85%
“…is not progressing, so the patient's thyroid cancer will not cause a problem. As a result, microinvasive papillary cancer is not considered even to be malignant [7][8][9][10][11]. According to the results of our study, microinvasive papillary cancer was detected in 26 patients, but of them were found incidentally in goiters with no cancer suspicion preoperatively.…”
Section: Journal Of Endocrinology and Thyroid Researchmentioning
confidence: 85%
“…20 Another study by Estebe et al reported that an intraoperative FS has higher sensitivity and specificity compared to a preoperative fine needle aspiration cytopathology (FNAC). 21 These authors also concluded that intraoperative FS reduced the number of unjustified total thyroidectomies and the need for two-staged procedures (conservative hemithyroidectomy followed by completion thyroidectomy). 21 The absence of high-risk features of PTC, by either pre-or intra-operative biopsy, could have down-staged a number of patients in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…21 These authors also concluded that intraoperative FS reduced the number of unjustified total thyroidectomies and the need for two-staged procedures (conservative hemithyroidectomy followed by completion thyroidectomy). 21 The absence of high-risk features of PTC, by either pre-or intra-operative biopsy, could have down-staged a number of patients in our cohort. Fifteen patients who underwent total thyroidectomies without the identification of a single high-risk feature were potentially suitable for initial hemithyroidectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Determining exactly which patients with a history of thyroid cancer have a low risk to be used as donors for transplantation Accuracy 68%-83% sensitivity, 83%-100% specificity, 82%-94% accuracy [10][11][12] 36-86% sensitivity, 100% specificity, 88% accuracy 13,14 Complications Localized bleeding, 15 nodule infarction Operating room needed with dedicated personnel and mobilization of donor required a All cases were carried out in different centers with few with adequate documentation; therefore, we report time as described by the Italian health system schedules of charges.…”
Section: Discussionmentioning
confidence: 99%
“…Data in literature show mostly comparable diagnostic properties between the 2 procedures, with no clear advantage of one over the other. [10][11][12][13][14] Certain postbiopsy procedure complications can also have serious consequences for donor management. Total thyroidectomy has a known surgical risk of bleeding ranging from 0.1% to 14%, 16,17 which may even cause hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%